117PCorrelation of MRI derived parameters and SUV uptake obtained from FDG- PET-CT with human papillomavirus status in oropharyngeal squamous cell carcinomas. (7th November 2019) - Goyal, S; Koyyala, V P B; Jajodia, A; Chaturvedi, A; Gairola, M; Rao, A; Sharma, M; Pasricha, S; Alhawat, P; Mahawar, V; Amrith, B; Tripathi, R
Abstract: Background: A favorable response to (chemo) radiotherapy (CCRT) is seen in human papillomavirus (HPV)-positive OPSCC patients. Apparent diffusion coefficient (ADC) derived from MRI has shown to predict treatment response. We evaluated the correlation between clinico-demographic profile of oropharyngeal squamous cell carcinomas patients (OPSCC patients) HPV status and ADC values, SUV uptake obtained from FDG- PET-CT. Methods: The study population was obtained from a historical cohort diagnosed with HPV-related OPSCC. A total of 105 OPSCC patients who had undergone molecular testing for HPV status by p16 with Immuno-histochemistry (IHC) were identified. 96 patients had pretreatment imaging (either PET-CT or MRI) and post CCRT imaging was included. Imaging was evaluated by head and neck radiologists to calculate mean ADC and SUV max. Pearson Chi- Square and ANOVA analyses were performed to evaluate the correlation. Results: 26 OPSCC were HPV-positive. HPV-positive HNSCC showed significantly association with smoking, grade & stage of the tumor, T status, Response to CCRT, lymph nodes, and ADC values on follow up imaging. Conclusions: In OPSCC patient's positive HPV status correlates with follow up mean apparent diffusion coefficient. The complimentary prognostic value of post treatment apparent diffusion coefficient might be partially ascribed to patients with a positive HPV status. Further studies are reasonable to determine whether PET-CT is a useful imaging biomarker in comparison to ADC to risk-stratify patients with HPV-related OPSCC. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.